Projets et conception de l’entrée monumentale de la cathédrale Sainte-Marie d’Auch : les apports du De re aedificatoria d’Alberti - Sophie Fradier (Les Cahiers de Framespa)
The construction of the monumental entrance to the Saint Mary of Auch Cathedral spans just over a century from 1560 to 1680. A number of labour contracts exist illustrating the completion of the work (17th Century) but few documents describe the initial construction phase (16th Century). By identifying the sources, both documentary and figurative, that characterize the artistic culture of this period, we can understand what kind of architectural language was being developed. But above and beyond the question of integrating and adapting theoretical models, the simultaneous study of the construction site of Saint Mary of Auch and the/De re aidificatoria/ d’Alberti enables us to define how the treaty actually influenced practice. We shall try to identify the thought process behind the engraving, design and production in the construction of the monumental entrance to Auch Cathedral.